Social Indicators: A Comparison Among Selected Countries. (July 2019) - Iqbal, Badar Alam; Rahman, Mohd Nayyer; Hasan, Munir
Abstract: The difference between growth and development is not subtle but substantially huge and the gap is ever increasing. The dividing line is social indicators. Countries witnessing high growth rates for decades are not equal performers in development when social indicators are observed. India is an emerging economy on the one hand and a developing on the other hand but a lower income country as per World Bank statistic. While India holds economic indicators that appears to be promising to the world and investors that is not the case with social indicators. The present study is an attempt to critically review the social indicators for India and to trace the trajectory of fall or growth in such indicators while comparing with selected countries.